2015
DOI: 10.4193/rhin14.070
|View full text |Cite
|
Sign up to set email alerts
|

Sinonasal malignancies in Sweden 1960-2010; a nationwide study of the Swedish population

Abstract: We found that the incidence for SNM has decreased during the study period 1960 through 2010, except for SNMM that has increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
1
5
1
Order By: Relevance
“…In about 50% of cases, tumors originated in the nasal cavities, followed by the maxillary (20%) and ethmoid sinuses (20%). A similar distribution was found in two population‐based studies carried out in the Netherlands and Sweden …”
Section: Discussionsupporting
confidence: 84%
“…In about 50% of cases, tumors originated in the nasal cavities, followed by the maxillary (20%) and ethmoid sinuses (20%). A similar distribution was found in two population‐based studies carried out in the Netherlands and Sweden …”
Section: Discussionsupporting
confidence: 84%
“…In contrast to malignant sino-nasal tumours (malignant melanoma excluded) which have decreased over the decades [ 16 ], we found an increase of IP over time: In the 60’s, the incidence was very low (0.008), but from the 70’s, there has been a fivefold increase (0.006–0.033), an increase which has not been shown earlier. This may be a true increase.…”
Section: Discussioncontrasting
confidence: 73%
“…A remarkable exception in this study was Denmark: the incidence rates for both men and women were the highest and showed a slowly increasing trend for both sexes . In a long‐term population‐based study from Sweden (1960‐2010), it was found that the incidence of sinonasal cancer decreased, with an exception for melanoma . Based on data from the Surveillance, Epidemiology, and End Results registry, in the United States (1973‐2011), the crude incidence of sinonasal cancer seemed to be 8.3/1 000 000 per year .…”
Section: Discussionmentioning
confidence: 53%
“…3 In a long-term population-based study from Sweden (1960-2010), it was found that the incidence of sinonasal cancer decreased, with an exception for melanoma. 13 Based on data from the Surveillance, Epidemiology, and End Results registry, in the United States (1973-2011), the crude incidence of sinonasal cancer seemed to be 8.3/1 000 000 per year. 14 In the period 1973-2006, the overall crude incidence remained relatively constant around 5.6/1 000 000 with a male-female ratio of 1.8.…”
Section: Trends In Incidencementioning
confidence: 99%